(untitled) (Open Academia: Journal of Scholarly Research, 2026)
ensuring road traffic safety is one of the priority directions in the domestic policy of any state. This field directly serves to protect human life and health, ensure public safety, and contribute to stable socio-economic development. In the Republic of Uzbekistan, large-scale institutional and legal reforms have been implemented in recent years to ensure road traffic safety. At the same time, the need to improve administrative-legal regulation mechanisms in the field of road traffic remains relevant. The application of existing legislation, prevention of violations, and the effectiveness of liability measures require scientific analysis. In particular, improving the legal status and powers of the State Road Traffic Safety Service operating within the internal affairs bodies system is of urgent importance. The purpose of this article is to analyze the current state of administrative-legal mechanisms in ensuring road traffic safety in the Republic of Uzbekistan and to develop scientifically grounded proposals for their development